Conformational Analysis And Vibrational Spectroscopic Investigation Of L-Proline-Tyrosine (L-Pro-Tyr) Dipeptide - Kecel, Serda; Özel, Ayşen; Çelik, Sefa; Agaeva, Gulshen; AKYÜZ, SEVİM (Elsevier Science Bv, Po Box 211, 1000 Ae Amsterdam, Netherlands, 2011)
In this study the conformational properties of the drug based dipeptide L-proline-L-tyrosine (Pro-Tyr) in its monomeric and dimeric forms, have been investigated by molecular mechanic and ab initio calculations. The energy calculations on Pro-Tyr dipeptide as a function of side chains torsion angles, enable us to determine their energetically preferred conformations. One-hundred and eight possible conformations of Pro-Tyr dipeptide have been investigated by conformational analysis and the low energy conformations of dipeptide have been determined by using the Ramachandran maps. Afterwards, the geometrical parameters of obtained stable conformations were used as starting parameters for quantum chemical calculations. The molecular structure of Pro-Tyr dipeptide, in the ground electronic state (in vacuum) was optimized by density functional theory method with B3LYP functional and using 6-31G(d,p) and 6-31++G(d,p) basis sets. The dimeric forms of the dipeptide were also formed and energetically preferred conformations of dimers were investigated using the same method and the same level of theory by using 6-31G(d,p) basic set. The fundamental vibrational wavenumbers, IR intensities and Raman activities of the global conformation of monomeric and dimeric forms of the dipeptide were calculated and compared with the experimental vibrational spectra of solid Pro-Tyr dipeptide. The total energy distributions (TED) of the vibrational modes were calculated by using Scaled Quantum Mechanical (SQM) analysis. Vibrational assignment was performed on the basis of calculated total energy distribution (TED) of the modes. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: conformational analysis; density functional theory; dipeptide; IR and raman spectra; proline; tyrosine ab-initio; raman-spectroscopy; peptide models; FT-IR; conformers; DFT; konformasyon analizi; yoğunluk fonksiyonu teorisi; IR ve Raman spektrumları; prolin; tirozin ab-initio; raman-spektroskopisi; peptid modelleri; konformerler